Tuning and Performance Analysis of Second-Order Linear Active Disturbance Rejection Controller for Trajectory Tracking and Balancing the Rotary Inverted Pendulum - Janeshwaran Gunasekaran; Ezhilarasi Deenadayalan (Engineering Proceedings, 2025)
Second-order Linear Active Disturbance Rejection Controller (SLADRC) is a powerful control technique. Ongoing research is focused on simplifying tuning procedures, extending applicability to handle more complex systems, and ensuring efficient real-time implementation. In this proposed work, four different tuning approaches, using the Atomic Orbital Search (AOS) optimization algorithm concerning the number of tuning parameters, are presented. The performance of each tuning method for stabilizing the rotary inverted pendulum in the upright position and tracking trajectory is analyzed and validated through simulation and experimentation. The results indicate that the reduced number of SLADRC controller parameters tuned using AOS optimization provides superior performance compared to the controller with more tuning parameters for the nonlinear rotary inverted pendulum. From the analysis method, II tuning, <semantics>b0, ωc, and k</semantics> provide the optimum results of settling time (<semantics>Ts</semantics>), 1.5 s, and maximum angle deviation of <semantics>θ<mfenced separators="|">3.8°</mfenced>, α(3°)</semantics>.